Analyzing the Factors Affecting Purchase Intention of Drugstore Beauty Products - Maharani, Regita; Pangaribuan, Christian Haposan (APPS Publications, 2021)
Objective – The objective of this study is to identify the key elements of buying beauty products in drugstore chains, discuss the reasons and factors behind why these drugstore chains had become the customers’ preference to visit and purchase beauty products, and to find out the relation of store convenience of drugstore chains to purchase intention of their beauty products. Methodology – The method used in this research is quantitative using an online survey started in November 2020. From 132 distributed questionnaires using Google Form link, only 106 responses are valid. Findings – The results reveal that shopping enjoyment and competitive price to have a significant influence on intention to purchase. However, the relationship between convenience and purchase intention was not supported. Novelty – Previous studies have predominantly examined the main effect of shopping convenience on purchase intention. This study extends our understanding of this relationship by highlighting the non-significant result in the convenience–intention linkage.